SYSTEM FOR PREDICTING THE PROBABILITY OF DEVELOPING RESPIRATORY FAILURE IN CHRONIC MECHANIC BRONCHITIS - Николай Иванович Панев; Сергей Николаевич Филимонов; Ольга Юрьевна Коротенко; Роман Николаевич Панев; Наталья Александровна Евсеева; Наталия Яковлевна Панева; Наталья Александровна Ефименко; Фаина Анисимовна Лузина (Медицина в Кузбассе)
Subject. 433 workers of coal mines of the South of Kuzbass (drifters, stope miners, operators of rock removing machines) were examined at the age of 40 to 54 with a previously established diagnosis of chronic mechanic bronchitis.